Erbium-Doped Fiber Laser With a Microfiber Coupled to Silica Microsphere - Sulaiman, Azlan; Harun, Sulaiman Wadi; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2012)
A compact erbium-doped fiber laser (EDFL) is demonstrated using a piece of 1.5-m-long erbium-doped fiber (EDF) with a microfiber coupled to a silica microsphere at the output end. A stable laser output is achieved due to the recirculation of amplified spontaneous emission (ASE) light inside the linear cavity and the incorporation of microsphere which serves as both a laser filtering element and a mirror. The laser operates at 1533.5 nm with a peak power of 7.7 dBm and an optical signal-to-noise ratio (OSNR) of around 24.4 dB with 980 nm pumping of 100 mW and a sphere diameter of 137 μm. The operating wavelength can be tuned down from 1533.4 to 1531.24 nm by changing the sphere diameter from 108.3 to 190.0 μm. The highest Q-factor of 12760 is obtained at the smallest sphere diameter of 108.3 μm.